A RISK-LEVEL ANALYSIS OF INTRA-COMMUNAL VIOLENCE A CASE STUDY OF UVWIE LOCAL GOVERNMENT AREA, DELTA STATE NIGERIA - Apanapudor, Joshua S.; Okpako, Sylvester O.; Okposo, Newton O.; Okwonu, Friday Z. (FUDMA JOURNAL OF SCIENCES, 2024)
Intra-communal violence perpetrates across various families and factions in a community and this is strongly supported by the undeniable solidarity felt and exhibited by the violent parties for their respective groups. In this research work, we made some assumptions regarding the violence risk level of the human community. Basic mathematical analyses such as the violence-free and the violent-persistent equilibrium points and the basic reproduction number were examined. As a case study, an analysis of the violence risk level of Uvwie local government, Delta State, Nigeria, was carried out, and the data collected via questionnaires revealed that the community is at high risk level of violence, and so violence will occur in most cases. The violence risk level and the peace level perceptions of various categories of the residents of the community were clearly presented and analyzed. The computational software used in this research was the Version 12 Mathematica Programming Software.